New perspectives on Adobe dreamweaver CS6 comprehensive - Hart, Kelly; Geller, Mitch (Course Technology, Cengage Learning, 2013)
Offers a critical-thinking approach to teaching Web design. This book explains and reinforces design software concepts and skills through the New Perspectives' signature case-based, problem-solving pedagogy